Clinical practices and medical students motivation - Salazar Blanco, Olga Francisca (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Clinical practices integrate learning and strengthen professional skills. It was propose to understand the factors that influence the motivation of medical students in clinical courses. This is a qualitative study following the Grounded Theory method and the interpretative framework of Symbolic Interactionism. 17 semi-structured interviews were conducted and 70 practices were observed. The practices emerged as motivating experiences that connected the learning, interests, emotions and relationships of students and reinforced intrinsic motivation and autonomous motivation. In conclusion, practices are motivating experiences that favor integral formation and self-regulation of learning.